The physiological impact of upper limb position in prone restraint. (July 2013) - Barnett, Richard; Hanson, Paul; Stirling, Chris; Pandyan, Anand D
Deaths occurring during and/or in close proximity to physical restraint have been attributed to positional asphyxia. This study investigated the physiological impact of three recognized prone-restraint positions with participants remaining passive. Position 3 (P3) the supported prone position (SPP) was designed to reduce the extent of pressure on the anterior chest wall (PAC) by bringing the upper limbs underneath the shoulder joint whereas for the other two positions (P1 and P2) the arms were abducted from the torso. Twenty-five adults participated. Forced vital capacity (FVC), expiratory volume in one second (FEV1), heart rate (HR) and oxygen saturations (SpO2 ) were taken three times in an upright seated position (baseline) and in each prone position. Mean PAC was measured at 102.6 (±24.3) and 101.4 (±24.4) mmHg for P1 and P2, respectively; however, in the SPP (P3) the mean PAC pressure reduced to 72.7 (±16.9) mmHg. All three prone-restraint positions reduced FVC and FEV1 compared with baseline ( P < 0.001). P1 and P2 where the arms were abducted reduced respiratory measures equally but differed from the SPP position ( P < 0.001) where PAC was significantly lower. Reductions in FVC from baseline were 16% for P1 and P2, and 11% for the SPP (P3) where PAC was ∼28% lower than in P1 and P2. Reductions in FEV1 were similar in all three prone-restraint positions and HR and SpO2 were unaffected. In summary, all prone-restraint positions restrict respiratory function but the risk associated with the position reduces as the PAC reduces.